Implementation of the Index Card Match Method to Increase Students' Interest in Class X ICT Subject at SMK Ibnu Kholdun Al-Hasyimi Even Semester for Academic Year 2020/2021 - Muhlishotun, Muhlishotun; Seituni, Siti; Yuliana, Dyan (Holistic Science, 2023)
According to field observations conducted at the Ibn Kholdun Al-Hasyimi Vocational School, it was found that learning still uses the dominant conventional method with the lecture method in explaining the material, students learn with textbooks, and do exercises from student worksheets. The teacher has not used learning media that is in accordance with the complexity of the material presented. Understanding of the concept of learning materials is still low, feelings of liking for learning situations, feelings of liking for student activities and student activity in class during the learning process. Learning in class X SMK Ibnu Kholdun Al-Hasyimi is still generally with lecture method learning, so students are less enthusiastic in accepting learning and cause boredom. Besides this, conditions that do not support learning often occur, students' attention is also low, in the teaching and learning process students are less enthusiastic because learning makes students inactive. Based on the above background, in this study the problem raised is whether the application of the Index Card Match method to increase student interest in learning for class X students in Information and Communication Technology subjects at Ibnu Kholdun Al-Hasyimi Vocational School in the even semester of the 2020/2021 academic year? The research design uses classroom action research. The research was determined by the location at the Ibn Kholdun Al-Hasyimi Vocational School. The location of the research was determined by Ibn Kholdun Al-Hasyimi Widoropayung, which is located at Jalan KP. School RT/RW 02/01 Widoropayung Village Besuki Situbondo. Data collection is observation, interview and documentation. Data analysis Analysis of students' interest in learning basic programming questionnaire data. Based on the results of the research and discussion, it can be concluded as follows: there is an increase in student interest in learning reaching 30% from 65% of the first cycle, an increase of 30% in the second cycle of class X subjects of Information and Communication Technology at Ibnu Kholdun Al-Hasyimi Vocational School in the even semester of the 2020/2021 academic year.